The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.18296/set.0363
|View full text |Cite
|
Sign up to set email alerts
|

How do teachers use picture books to draw on the cultural and linguistic diversity in their classrooms?

Abstract: Picture books are ubiquitous in Western early childhood and primary settings. This article explores how picture books are being used in culturally and linguistically diverse settings, by describing and exploring the practice of two New Zealand teachers who use picture books extensively in their classrooms. Findings from interviews, observations, reflections, and collaborative workshops indicate the power of picture books within a diverse classroom population and the importance of several factors: the personal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…While the educators' teaching experience varied from less than five to close to 30 years, with some having several years' experience in culturally and linguistically diverse settings, they were not found to promote culturally responsive practice when using children's books. This is in contrast to the findings of Blakeney-Williams and Daly [39] who found that some experienced educators working in culturally and linguistically diverse education settings can promote inclusive practice even when using books that do not reflect diverse cultures and languages when they "help children to make connections between the ideas in picture books and their own worlds" [39] (p. 49). However, the educators in this study largely assumed shared understandings of all children and did not encourage or model the making of connections to the diverse lives and backgrounds of the children.…”
Section: Book Reading Practices: the "Othering" Of Those From Minority Backgroundscontrasting
confidence: 65%
See 2 more Smart Citations
“…While the educators' teaching experience varied from less than five to close to 30 years, with some having several years' experience in culturally and linguistically diverse settings, they were not found to promote culturally responsive practice when using children's books. This is in contrast to the findings of Blakeney-Williams and Daly [39] who found that some experienced educators working in culturally and linguistically diverse education settings can promote inclusive practice even when using books that do not reflect diverse cultures and languages when they "help children to make connections between the ideas in picture books and their own worlds" [39] (p. 49). However, the educators in this study largely assumed shared understandings of all children and did not encourage or model the making of connections to the diverse lives and backgrounds of the children.…”
Section: Book Reading Practices: the "Othering" Of Those From Minority Backgroundscontrasting
confidence: 65%
“…Many of these educators also aim to assimilate children into the dominant culture, often viewing the children's own backgrounds as "burdens" or challenges and thus teaching about diversity can often be superficial or tokenistic [26,38]. In addition, some educators mistakenly believe that one book about a particular cultural group is adequate to portray that group's viewpoints and perspectives [39]. Such beliefs can influence the curriculum decisions made by educators thus potentially further contributing to practices that may unwittingly reinforce a perception of the dominant culture as being preferable or superior.…”
Section: Challenges In Addressing and Responding To Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…According to Blakeney-Williams and Daly [43], teachers tend to choose picture books with strong personal resonance because it models students' personal engagement and attachment with books and conveys to students how important books can be in people's lives. Similarly, instructors in this interview cited personal interests as a major influence in selecting cultural-diversitythemed picture books.…”
Section: Teachers' Interestmentioning
confidence: 99%
“…Such a multifaceted systematic picture book selection process has been proved by other researchers as beneficial as it ensures that student engagement with these carefully selected picture books can be maintained at a high level. First, a teacher's enthusiasm for a book inspires his/her students to read the book and seek out other materials on the book's topics [43,[53][54][55]. When the book topic is on cultural diversity, students are likely to be motivated to search for more information about an unfamiliar culture.…”
Section: Multifaceted Considerations In Selecting Picture Booksmentioning
confidence: 99%